Safety and Long-Term Efficacy of Transition from Sildenafil to Tadalafil due to Side Effects in Patients with Pulmonary Arterial Hypertension - Lichtblau, Mona; Harzheim, Dominik; Benjamin, Nicola; Marra, Alberto M.; Grünig, Ekkehard; Egenlauf, Benjamin (Lung, 2015)
IntroductionTwo phosphodiesterase-type 5 (PDE-5) inhibitors, sildenafil and tadalafil, are approved for treatment of pulmonary arterial hypertension (PAH). It has not yet been observed if transition from sildenafil to tadalafil is beneficial in patients suffering from adverse reactions. Aim of this study was to analyze safety and long-term effects in PAH patients whose treatment was transitioned from sildenafil to tadalafil due to intolerable side-effects.MethodsA retrospective analysis of PAH-patients who were stable on sildenafil for >3 months and transitioned to tadalafil due to adverse events was performed. Data collected included demographics, PAH-etiology, WHO-functional class, 6 min walking distance (6MWD), echocardiography, lung function tests, and NTproBNP pre-transition and 3, 6, and 12 months post-transition.ResultsIncluded were 13 PAH patients (8 females mean age 64 ± 10 years) who had been on sildenafil for a mean of 12 ± 8.4 months. In six patients (46.1 %) a switch to tadalafil was feasible and resulted in tolerable side effects and a stable clinical course with improvement of symptoms, 6MWD, stable echocardiographic findings, and NTproBNP-levels during a follow-up of 11 ± 3 months. In 5 out of 13 patients (38.5 %) adverse events occurred under tadalafil as well and therapy with PDE-5 inhibitors was discontinued. In two patients (15.4 %) sildenafil-treatment could be successfully restarted after an intermittent switch to tadalafil.ConclusionsThe observations of this study indicate that a transition of sildenafil to tadalafil in case of intolerable side effects is a reasonable therapy option in about 50 % of the patients. These results should be verified by a larger prospective study.